2022 Workshop on Fault Detection and Tolerance in Cryptography (FDTC) 2022
DOI: 10.1109/fdtc57191.2022.00012
|View full text |Cite
|
Sign up to set email alerts
|

The More You Know: Improving Laser Fault Injection with Prior Knowledge

Abstract: We consider finding as many faults as possible on the target device in the laser fault injection security evaluation. Since the search space is large, we require efficient search methods. Recently, an evolutionary approach using a memetic algorithm was proposed and shown to find more interesting parameter combinations than random search, which is commonly used. Unfortunately, once a variation on the bench or target is introduced, the process must be repeated to find suitable parameter combinations anew.To nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In practical experiments, various methods can be employed to inject faults [26][27][28][29][30][31][32][33][34], including variations in the operational voltage, clock, or temperature of the circuit, electromagnetic pulse interference with circuit operation, utilization of laser, UV-ray, X-ray, or focused ion beam (FIB), etc. In addition to this, the rest of the key recovery processes are all accomplished through computer computations.…”
Section: Experiments About Our Combined Analysis On Picomentioning
confidence: 99%
“…In practical experiments, various methods can be employed to inject faults [26][27][28][29][30][31][32][33][34], including variations in the operational voltage, clock, or temperature of the circuit, electromagnetic pulse interference with circuit operation, utilization of laser, UV-ray, X-ray, or focused ion beam (FIB), etc. In addition to this, the rest of the key recovery processes are all accomplished through computer computations.…”
Section: Experiments About Our Combined Analysis On Picomentioning
confidence: 99%
“…So, in essence, the simulators consider all models indiscriminately or the developer is left to decide. AI models could be used to inform the choice of the parameters for the test cases as done by [7] and [19] which showed that a certain combination of parameters leads to an increase in the number of exploitable faults. A successful AI model would be able to eliminate (to an extent) less probable fault models from the ones which occur more frequently.…”
Section: Informed Fault Explorationmentioning
confidence: 99%
“…Their solution to narrow down the space of exploitable locations from the vulnerable locations could be beneficial. Krcek et al [19] utilizes genetic algorithms and machine learning to develop a solution that allows them to find more exploitable faults compared to using either of the approaches.…”
Section: Introductionmentioning
confidence: 99%